Genome-Wide Profiling of Histone Modifications in Fission Yeast Using CUT&Tag - Torres-Garcia, Sito; Huang, Yiwen; Dewornu, Felix Selasi; Tong, Pin; Yeboah, Rebecca; Allshire, Robin; Shukla, Manu (Methods in molecular biology (Clifton, N.J.), 2025)
Eukaryotic DNA is organized in the nucleus in the form of chromatin. Nucleosomes, the fundamental unit of chromatin, are subject to many posttranslational modifications (PTMs) as well as compositional variations through incorporation of histone variants. These alterations play important roles in regulation of genome structure and activity. Genome-wide profiling of these regulatory features is essential for understanding of genome function. Chromatin immunoprecipitation coupled with next-generation sequencing (ChIP-Seq) is a widely used method to assay genome-wide localization in fission yeast but suffers from the requirement for a large amount of input chromatin, antibodies, and a cumbersome experimental pipeline. New methods such as Cleavage Under Targets and Tagmentation (CUT&Tag), which combine the specificity of targeted cleavage and adapter insertion with the sensitivity of next-generation sequencing, enable identification and characterization of various epigenetic marks affording low input requirement as well as more streamlined protocols. However, these approaches have not been adapted for use in fission yeast, Schizosaccharomyces pombe. Here, we describe an adapted CUT&Tag protocol for epigenomic profiling in fission yeast using the heterochromatin-associated histone H3K9 methylation PTM for benchmarking.